2015
DOI: 10.1186/s12885-015-1808-6
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB p65 and p50 homodimer cooperate with IRF8 to activate iNOS transcription

Abstract: BackgroundInducible nitric oxide synthase (iNOS) metabolizes L-arginine to produce nitric oxide (NO) which was originally identified in myeloid cells as a host defense mechanism against pathogens. Recent studies, however, have revealed that iNOS is often induced in tumor cells and myeloid cells in the tumor microenvironment. Compelling experimental data have shown that iNOS promotes tumor development in certain cellular context and suppresses tumor development in other cellular conditions. The molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 60 publications
8
44
0
Order By: Relevance
“…The target genes of Irf8 include Fas, Bax, FLIP, STAT1 and iNOS, suggesting an essential role of Irf8 in apoptosis. 58-62 Consistently, knockdown of Irf8 attenuated cisplatin-induced apoptosis in RPTC cells (Figure 7). Thus, hypomethylation of Irf8 during cisplatin-induced AKI may lead to the up-regulation of this pro-apoptotic transcription factor for tubular cell injury and death.…”
Section: Discussionsupporting
confidence: 54%
“…The target genes of Irf8 include Fas, Bax, FLIP, STAT1 and iNOS, suggesting an essential role of Irf8 in apoptosis. 58-62 Consistently, knockdown of Irf8 attenuated cisplatin-induced apoptosis in RPTC cells (Figure 7). Thus, hypomethylation of Irf8 during cisplatin-induced AKI may lead to the up-regulation of this pro-apoptotic transcription factor for tubular cell injury and death.…”
Section: Discussionsupporting
confidence: 54%
“…It was reported that several key genes in the inflammatory process such as NF- κ B provide a mechanistic link between inflammation and cancer [4548]. Activation of TLRs and TNFR leads to NF- κ B activation and induced the expression of many proinflammatory molecules including NO synthase 2 (iNOS) [49, 50]. A growing number of studies have reported the key role of TLR4/NF- κ B/TNF- α signaling to promote tumor growth in experimental models of colitis associated cancer [44, 5153], whereas data from human CAC are rare.…”
Section: Discussionmentioning
confidence: 99%
“…In myeloid cells, particularly in macrophages, TNFα and LPS/TLR ligands-activated NF-κB is a major regulator of iNOS expression (27, 28, 42, 43). NF-κB, once activated by LPS or TNFα, can activate iNOS expression (28, 44). The p65 and p50 homodimers of the canonical NF-κB directly binds to the nos2 promoter region to activate nos2 transcription in myeloid cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB, once activated by LPS or TNFα, can activate iNOS expression (28, 44). The p65 and p50 homodimers of the canonical NF-κB directly binds to the nos2 promoter region to activate nos2 transcription in myeloid cells (28). In addition to NF-κB, inflammatory cytokines such as IFN-γ have also been shown to regulate iNOS expression (27, 45).…”
Section: Discussionmentioning
confidence: 99%